1992
DOI: 10.1042/bj2810301
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated increases in cytosolic Ca2+ in the human erythroleukaemia cell line involve pertussis toxin-sensitive and -insensitive pathways

Abstract: The pluripotent human erythroleukaemia cell line, HEL, possesses erythrocytic, megakaryocytic and macrophage-like properties. With respect to signal transduction, HEL cells have been used as a model system for platelets, but little attention has been paid to their phagocytic properties. We studied the effects of various receptor agonists on the intracellular free Ca2+ concentration ([Ca2+]i) in HEL cells. Thrombin, platelet-activating factor (PAF), ATP, UTP, prostaglandins E1 and E2 (PGE1 and PGE2), the PGE2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…This suggests that both nucleotides act through a common nucleotide receptor, most likely of the P 2U purinoceptor subtype. Consistently, the presence of receptors in HEL cells for UTP and ATP has been shown in earlier studies (28). As shown above, UTP did not depend on extracellular Ca 2ϩ to evoke its effects, suggesting that the receptor for UTP is not ionotropic (such as P 2 receptors of the X subtype).…”
Section: P 2u Purinoceptors Couple To G 16 To Mobilize Intracellular supporting
confidence: 66%
See 3 more Smart Citations
“…This suggests that both nucleotides act through a common nucleotide receptor, most likely of the P 2U purinoceptor subtype. Consistently, the presence of receptors in HEL cells for UTP and ATP has been shown in earlier studies (28). As shown above, UTP did not depend on extracellular Ca 2ϩ to evoke its effects, suggesting that the receptor for UTP is not ionotropic (such as P 2 receptors of the X subtype).…”
Section: P 2u Purinoceptors Couple To G 16 To Mobilize Intracellular supporting
confidence: 66%
“…2B). PGE 2 , which acts via G i -coupled receptors (28), was completely ineffective after PTX treatment, demonstrating that PTX treatment was exhaustive (not shown). The similar relative inhibitions of agonist-induced Ca 2ϩ changes that were observed after PTX treatment in parental and G ␣16 -suppressed cells make it unlikely that the expression pattern of G ␣ -and G ␤␥ -sensitive PLC-␤ isoforms differed considerably between G ␣16 -suppressed cells and parental HEL cells.…”
Section: Utp-dependent Ca 2ϩ Mobilization Is Abrogated In G ␣16mentioning
confidence: 98%
See 2 more Smart Citations
“…3b, iloprost gen- hydrolysis. In previous studies, PGI, or its analogues evoked an increase in the cytosolic Ca2+ concentration in human cell lines, MEG-01 cells [8], and HEL cells, a pluripotent human erythroleukaemia cell line [19]. The present study revealed that the human PGI, receptor as well as the mouse receptor can couple to multiple signalling pathways, adenylate cyclase and phospholipase C. sequence of the human PGI, receptor is 73% identical to that of the mouse receptor.…”
Section: Resultsmentioning
confidence: 82%